A Facile Transition Metal‐Free Ionic Liquid [BMIM]OH Mediated Regio‐ and Stereoselective Hydrocarboxylation of Alkynylnitriles. Issue 3 (16th December 2020) - Kumari, Chandresh; Goswami, Avijit
Abstract: We report an efficient and straight forward access to nitrile substituted enol esters via ionic liquid [BMIM]OH mediated hydrocarboxylation of alkynylnitriles under mild conditions. This atom economical transition metal‐free protocol gives an easy access to a variety of such enol esters with excellent regio and Z ‐stereoselectivity. Reusability of [BMIM]OH without losing of significant amount of yield is another noticeable feature of this article. Abstract : An atom economical and transition metal‐free, green methodology for the synthesis of nitrile substituted Z ‐enol esters via ionic liquid [BMIM]OH mediated hydrocarboxylation of alkynylnitriles is reported.